The Influence Of Husband's Positive Affirmations On The Pain Levels Of Women Giving Birth In The Inpartu In Hospital National Guido Valadares Dili Timor Leste - Amelia Da Cruz; Andariningsih (Journal for Research in Public Health, 2022)
Giving positive affirmations to the husband can minimize stress and depression during childbirth, because it is much easier for the mother to control her emotions, while the fetus feels emotional closeness and a stronger inner bond, because when giving positive affirmations from the husband, the mother and fetus establish subconscious communication, the baby is being born with relatively no shortage of oxygen, the husband felt calmer during the birth process. This research is a quasi-experimental research with a two group posttest design only approach. The population in this study was all mothers in the first stage of labor at the Hospital National guido valadares Dili Timor Leste in 2021, totaling 20 respondents. Samples were taken using accidental sampling technique. Variable independent in this research is the husband's positive affirmation and variable dependent level of maternal anxiety. This research was conducted at Hospital National guido valadares Dili timor leste and the measuring instrument in this study used a pain scale. The analysis in this research uses Mann statistical test analysis Whitney with α 0.05. After carrying out the Kolmogorov test, it was found that asymp sig was 0.016 < 0.05, meaning that the data was normally distributed and the Mann Whitney test could be carried out. Based on table 7, it was obtained after carrying out the Mann Whitney test was found that the research results obtained values significance (α) is 0.05 with a correlation coefficient of 0.013. Based on hypothesis testing using the Mann Whitney statistical tests with standards significance (α) = 0.05, it can be concluded that there is an influence of the husband's positive affirmation on the level of pain of women giving birth during birth at the hospital national guido valadares Dili timor leste in 2021 because of the value significance (ρ) 0,013 less than α =0,05 In this study, there was a significant difference between mothers who were given positive affirmations and those who were not given positive affirmations, namely in the group that was not given positive affirmations, most of them experienced severe pain, whereas in the birth mothers who were given affirmation positive Most experience moderate to mild pain.